A novel mass flow controller for tandem hot rolling mills. (August 2021) - Knechtelsdorfer, U.; Steinboeck, A.; Schausberger, F.; Kugi, A.
Abstract: In tandem hot strip rolling mills, the roll speed of the mill stands is synchronized to ensure a uniform mass flow. A uniform mass flow is desirable to keep the strip tension constant and thus avoid large movements of the loopers which are located between the mill stands in order to control the strip tension. This also improves the general thickness quality and prevents the strip from necking in case of too excessive strip tension. In typical state-of-the-art implementations, the roll speed is synchronized in a cascade master–slave control structure where the very last downstream mill stand serves as speed master and the upstream mill stands operate in a slave mode to make sure that the mass flow is kept constant. While the relation between the roll speeds in the classical synchronization control concept is typically constant, a thorough analysis of the mass flow reveals that the slip between the work rolls and the strip is time varying. Therefore, in order to ensure a uniform mass flow, a novel adaptive speed synchronization controller is proposed, which can be easily added to the existing control structure and is computationally undemanding. To this end, a mathematical model of the whole tandem mill including the complete control structure is derived and validated by measurements. Simulation results for this validated model prove that the proposed mass flow controller clearly outperforms the existing solution. Highlights: Validated mathematical model of strip thickness and velocity in tandem rolling mill. Speed measurements at looper rolls used for estimation of true slip in roll gaps. Adaptive mass flow controller improves speed synchronization between mill stands. Adaptive controller is added on top of existing cascade speed control structure. Efficacy and robustness of controller tested in simulation with the validated model.